Antioxidant Activity and Physicochemical Characteristics of Dry Noodles with a Mixture of Wheat Flour and Kidney Bean Flour With the Addition of Butterfly Pea (Clitoria Ternatea L.) Extract - Rina Yenrina; Ismed Ismed; Wina Hildayani; Jihan Rahma (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
This study aims to determine the antioxidant activity and physicochemical properties of dried noodles mixed with wheat flour and red bean flour with the addition of butterfly pea flower (Clitoria Ternatea L.) extract. The design used in this study used a completely randomized design (CRD) with 5 treatments and 3 replications. Data analysis using ANOVA and further test with Duncan's New Multiple Range Test (DNMRT) analysis at 5% level. The treatments used in this study were treatment A (20 ml water: 0 ml butterfly pea extract), B (15 ml water: 5 ml butterfly pea extract), C (10 ml water: 10 ml butterfly pea extract), D (water 5 ml: 15 ml butterfly pea extract), and E (0 ml of water: 20 ml of butterfly pea extract). The results of this study significantly affected the 5% level on the water content test, ash content, fat test, protein test, carbohydrates, antioxidant activity, and physical analysis of color. Based on the physical and chemical analysis of dried noodle products, the best treatment was in treatment C (addition of 10g telang flower extract) with a color test value of 232.98°Hue, an elasticity test of 26.50%, a moisture content of 6,36%, a ash 1.49%, fat content 2.14%, protein content 19.36%, carbohydrate content 70.63%, and antioxidant activity 33.32%.